Implementation of citizens' juries in Bogotá - Citizens' Juries in Bogotá (2024)
In the late 2022, we started our research activities revolving around the implementation of the Citizens‘ Juries in Colombia within the context of the Mitigate+. In the beginning of the project, the work consisted mainly of planning the Citizens‘ Juries conceptually (e.g., What components should the CJ have? What structure should it follow? How should participants ideally be invited?). The later planning stages were concerned with bringing the initial conceptual work to life. From the theoretical planning of the content from our desks, to the planning of the concrete design with the partners and local political authorities on site, to the actual implementation, many committed people were involved in the development process. With the help of these people, we were ultimately able to implement the Citizens‘ Juries on the weekends of May 25 & 26, and June 1-3. In this blogpost, we describe the process of preparing the Citizens‘ Juries, their actual implementation and the challenges the research team faced throughout the process.